Penerapan Kombinasi Metode Entropy dan SMART Dalam Pemilihan Kepala Divisi Keuangan - Muhamad Yusran; Adhie Thyo Priandika (Bulletin of Computer Science Research, 2025)
The election of the Head of the Finance Division is an important decision that requires an objective and systematic evaluation of the existing candidates. This study proposes the application of a combination of Entropy and SMART (Simple Multi-Attribute Rating Technique) methods to support the decision-making process in the election of the Head of the Finance Division. The Entropy method is used to objectively determine the weight of the criteria, based on the distribution of candidate assessment data, while the SMART method is applied to assess each candidate based on predetermined criteria. The results of the ranking of candidates for the Head of the Finance Division are based on the final score obtained by each candidate. Based on these results, candidate A5: Eko Prabowo ranks highest with a score of 0.6667, followed by A7: Gita Susanti with a score of 0.6097. These results show that Eko Prabowo is the most superior candidate to be considered as the Head of the Finance Division, based on the assessment method used in this study. The combination of these two methods allows for more accurate, transparent and accountable decision-making, as it is based on objective and structured calculations.